PENGEMBANGAN BUKU AJAR BA-CA BERBASIS METODE AHE UNTUK KELAS I SEKOLAH DASAR - Ariyanto, Cindy Stefanny Putri; Priyanto, Wawan; Subekti, Ervina Eka (Universitas Sarjanawiyata Tamansiswa, 2021)
This study aims 1) Knowing the characteristics of the BA-CA Textbook based on the Ahe Method. 2) Knowing, evaluating the validity and practicality of the Ahe Method-Based Textbook. This research is a research and development applied in the field of education. Research and Development (R & D) is the development and validation of Sugiyono's products using development procedures only up to product trials. The result of the validity test of the teaching material expert's assessment was 90.00, while the material expert's assessment was 81.81. The results of the practicality test for teacher response assessments with an average score of 92.18. The results show that the Textbook is valid and practical to be used for learning to read.